MAKNA TIGA IKON GAJAH DI DALAM GEREJA SAINT PIERRE AULNAY PRANCIS - Panji Syofiadisna (KALPATARU, 2020)
Abstract. Saint Pierre Aulnay Church is a Romanic-style church (Romanesque) that was built in the 12th century and is located in the Aquitaine Region, France. In this church, there are three elephant icons in the capital columns section. At the top of the icon, there is also an inscription in Roman that reads "HI SVNT ELEPHANTES" which means "this is an elephant-elephant". This unique sentence and elephant icon is not found in other Romanic-style churches in France. Elephants are not native to Europe, but elephant icons are produced in European (French) churches. During Medieval, some churches were found to have icons of animals or mythological creatures that were placed in several parts of the church. The icons of the animals are connected with the character of Jesus and are called bestiaries. The problem that will be answered in this research is what is the meaning contained in the elephant icon with the words "HI SVNT ELEPHANTES". The review in this study is the history of iconography and emphasizes the themes, concepts, styles, and meanings of icons. The theory used to analyze the problem put forward is the iconography and iconology of Erwin Panofsky. The results of this interpretation will be compared with the meaning of elephants in the archipelago at the same time. Keywords: Bestiary, Church of Saint Pierre Aulnay, Elephant Icon, Medieval, French, Physiologus, Jesus Abstrak. Gereja Saint Pierre Aulnay adalah gereja bergaya Romanik (Romanesque) yang dibangun pada abad ke-12 dan terletak di Region Aquitaine, Prancis. Di dalam gereja ini terdapat tiga ikon gajah pada bagian capital columns. Pada bagian atas ikon terdapat pula inskripsi dalam bahasa Romawi yang bertuliskan “HI SVNT ELEPHANTES” yang artinya “ini adalah gajah-gajah”. Uniknya kalimat dan ikon gajah ini tidak ditemukan pada gereja bergaya Romanik lain di Prancis. Gajah bukan hewan asli Eropa namun ikon gajah diproduksi di gereja Eropa (Prancis). Pada masa Medieval memang didapati sejumlah gereja memiliki ikon-ikon hewan atau makhluk mitologi yang ditempatkan pada beberapa bagian gereja. Ikon dari hewan-hewan itu terhubung dengan karakter Yesus dan dinamakan bestiary. Masalah yang akan dijawab pada penelitian ini yaitu apa makna yang terkandung pada ikon gajah dengan tulisan “HI SVNT ELEPHANTES”. Tinjauan dalam penelitian ini bersifat sejarah ikonografi dan ditekankan pada tema, konsep, gaya, serta makna dari ikon. Teori yang dipakai untuk menganalisis masalah yang dikemukakan adalah ikonografi dan ikonologi dari Erwin Panofsky. Hasil dari pemaknaan ini akan dibandingkan dengan makna gajah di nusantara pada masa yang sama. Kata kunci: Bestiary, Gereja Saint Pierre Aulnay, Ikon Gajah, Medieval, Physiologus, Yesus